The Relationship Between Antenatal Care Examination Results and The Incidence of Preeclampsia in Pregnant Women - Kalenggo, Nabila Syahrani; Rosdianah; Azizah Nurdin (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2024)
Maternal mortality is a significant health issue that remains a concern in Indonesia. The commonly used indicator for maternal mortality is the maternal mortality rate (MMR), which serves as the primary measure of the success of maternal health programs. One of the major contributing factors to maternal mortality is preeclampsia, and a factor influencing the incidence of preeclampsia is antenatal care visits. This is a quantitative study using an observational analytic design with a case-control approach. The sampling method used is purposive sampling. The sample size is 184, consisting of 92 cases and 92 controls that meet the inclusion and exclusion criteria. Data analysis was conducted using univariate and bivariate analysis with the chi-square test. Based on the chi-square statistical test results, the following P-values were obtained: 0.098 < 0.05 for the age variable, 0.761 < 0.05 for the parity variable, 0.000 > 0.05 for the blood pressure variable, 0.001 > 0.05 for the BMI variable, 0.014 > 0.05 for the urine protein variable, and 0.300 > 0.05 for the ANC visit frequency variable. The conclusion of this study is that there is a relationship between antenatal care examination results, namely blood pressure, maternal BMI, and maternal urine protein, and the incidence of preeclampsia. However, there is no relationship between age, parity, and the frequency of ANC visits and the incidence of preeclampsia at RSKD Ibu dan Anak Siti Fatimah Makassar from January 2020 to December 2022.